If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + 4)(x + 5) = 0 Reorder the terms: (4 + 5x)(x + 5) = 0 Reorder the terms: (4 + 5x)(5 + x) = 0 Multiply (4 + 5x) * (5 + x) (4(5 + x) + 5x * (5 + x)) = 0 ((5 * 4 + x * 4) + 5x * (5 + x)) = 0 ((20 + 4x) + 5x * (5 + x)) = 0 (20 + 4x + (5 * 5x + x * 5x)) = 0 (20 + 4x + (25x + 5x2)) = 0 Combine like terms: 4x + 25x = 29x (20 + 29x + 5x2) = 0 Solving 20 + 29x + 5x2 = 0 Solving for variable 'x'. Factor a trinomial. (5 + x)(4 + 5x) = 0Subproblem 1
Set the factor '(5 + x)' equal to zero and attempt to solve: Simplifying 5 + x = 0 Solving 5 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + x = 0 + -5 x = 0 + -5 Combine like terms: 0 + -5 = -5 x = -5 Simplifying x = -5Subproblem 2
Set the factor '(4 + 5x)' equal to zero and attempt to solve: Simplifying 4 + 5x = 0 Solving 4 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 5x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 5x = 0 + -4 5x = 0 + -4 Combine like terms: 0 + -4 = -4 5x = -4 Divide each side by '5'. x = -0.8 Simplifying x = -0.8Solution
x = {-5, -0.8}
| 4y+5y-2y=49 | | k=8k+2k | | 0.1y^3+0.5y^3-0.3y^3= | | 3x-2=3(x-0.66) | | -5/2-(2?10+7)=0 | | 5x-16=3(x+10) | | 5(2j+3)=25 | | n+2=-4n+2n+14 | | -4(x+6)+2=-40 | | z/9-9=4 | | 22x-5=6 | | 5(-21)-2y=-22 | | 9m+9+m=28+11 | | 4x+8=26 | | 3(2+4p)-5(3+p)=5 | | 25Y^2-10=0 | | -4x-3(7x+3)=166 | | -4(3x+2)=32 | | 4x-2=-2x+34 | | 3y+9=2y-8 | | 69=3x+4x+6 | | (2x+3x^2y)dx-(x^3-3y^2)dy=0 | | 15f+6+5f=86 | | 8x+9=141 | | (2+3xy^2)dx+(4x^2y)dy=0 | | -6+8y+4-5y= | | 4y-8+y=22 | | 106=x^2=x/2 | | t*6-4=14 | | 40+9=40+8 | | q=p-q/z | | 4x+10=11-10x |